Communication skills for managers - Chan, Janis Fisher (American Management Association, 2002)
Communicating clearly is a critical skill for successful managers! The ability to communicate clearly is the critical core competency for successful managers at all levels and in all industries. This book is your guide to business communication that delivers the message-whether written, or spoken, in person or via e-mail-with respect for the receiver, and in all business situations. This solid overview of all facets of business communication offers numerous opportunities to practice and apply your new skills and a log to track your improvement. Readers will learn how to: Communicate clearly a.